The Relationship Between Maternal Motivation and the Role of Health Workers in the Completion of Tetanus Toxoid Immunization for Pregnant Women - Liliek Pratiwi; Aticeh Aticeh; Mardeyanti Mardeyanti; Fauziah Yulfitria; Karningsih Karningsih; Nur Azizah (Indonesian Journal of Global Health Research, 2025)
Tetanus Toxoid (TT) immunization is a vital intervention for preventing maternal and neonatal tetanus. However, achieving complete TT immunization among pregnant women presents an ongoing challenge in various settings, notably within the Pangenan Health Center area of Cirebon Regency. Compliance with this preventive measure is hypothesized to be influenced by factors such as the performance of healthcare workers, maternal motivation, and the frequency of antenatal care (ANC) visits.This quantitative, cross-sectional study investigated the relationship between these three factors and the completeness of TT immunization in the Pangenan Health Center's service area. Data were collected from 36 pregnant women selected via accidental sampling and analyzed using the Chi-square test (with a significance level of α = 0.05).The findings indicated that 55.6% of the participants had received complete TT immunization. Bivariate analysis demonstrated statistically significant associations between complete TT immunization and: healthcare workers’ roles (ρ = 0.022), maternal motivation (ρ = 0.040), and ANC visit frequency  (ρ = 0.009). In conclusion, the study established a significant relationship between the roles of healthcare workers, maternal motivation, and the frequency of ANC visits and the completeness of TT immunization among pregnant women. To improve immunization coverage, the study recommends enhancing behavioral education, strengthening the capacity of healthcare providers, and ensuring optimal utilization of ANC services.